2022
DOI: 10.2196/38988
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Priorities in Developing Virtual Reality Programs for Core Nursing Skills: Cross-sectional Descriptive Study Using the Borich Needs Assessment Model and Locus for Focus Model

Abstract: Background There are limitations to conducting face-to-face classes following the recent COVID-19 pandemic. Web-based education is no longer a temporary form of teaching and learning during unusual events, such as pandemics, but has proven to be necessary to uphold in parallel with offline education in the future. Therefore, it is necessary to scientifically organize the priorities of a learner needs analysis by systematically and rationally investigating and analyzing the needs of learners for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Reality programs involve creating a program in the form of proceeds in the direction of the actual situation without writing scripts in advance. The program is in the form of realistic transactions which are necessary to prioritize needs of those who receive the real-life program systematically and have a reason [11]. Most reality programs are designed to accommodate this group in terms of learning, understanding and developing themselves in various forms [12,13].…”
Section: B Reality Programmentioning
confidence: 99%
“…Reality programs involve creating a program in the form of proceeds in the direction of the actual situation without writing scripts in advance. The program is in the form of realistic transactions which are necessary to prioritize needs of those who receive the real-life program systematically and have a reason [11]. Most reality programs are designed to accommodate this group in terms of learning, understanding and developing themselves in various forms [12,13].…”
Section: B Reality Programmentioning
confidence: 99%
“…Core nursing skills are essential as they are frequently used in the daily responsibilities of nurses and constitute a fundamental component of nursing education and training [ 5 , 6 ]. Core nursing skills are frequently used in the daily tasks of nurses and are fundamental elements of nursing education and training [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Core nursing skills are essential as they are frequently used in the daily responsibilities of nurses and constitute a fundamental component of nursing education and training [ 5 , 6 ]. Core nursing skills are frequently used in the daily tasks of nurses and are fundamental elements of nursing education and training [ 5 , 6 ]. It has been shown that nursing students’ experience with essential nursing skills enhances their clinical performance and leads to higher levels in education and collaboration, interpersonal relationships and communication, and professional development areas [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation